TRANSFORMASI GEGURITAN RAJAPALA DI ERA GLOBALISASI - Gede Yuli Sutrawan; I Nengah Duija; I Ketut Tanu (Pangkaja: Jurnal Agama Hindu, 2021)
Geguritan Rajapala can be seen in paintings, murals, name of streets, reliefs, name of places, name of a business, short films, Balinese Pop songs, dances, etc. The various transformations present us with half of the story, or in other words, the plot of Rajapala presented incompletely. Thus, it is really important to rise the Transformation of Geguritan Rajapala in the Globalization Era as the topic of research. The present research concerns three main problems, such as, (1) the narrative structure of Geguritan Rajapala; (2) the transformation form of Geguritan Rajapala in the globalization era; and (3) the values in Geguritan Rajapala. The theories used in this research were structural, semiotics, esthetics, and values theory. The present research is qualitative. The data collection was carried out by interview, library research, and document study. The results of the present research are, (1) the narrative structure of Geguritan Rajapala; (2) the transformation forms of Geguritan Rajapala; and (3) the values inside the Geguritan Rajapala.